Geriatric dentistry course effect against ageism among dental students: A cohort study - Mendes, Mariana Sarmet Smiderle [UNESP] (2025)
Purpose: The aim of this study is to investigate the effectiveness of geriatric dentistry courses as a combating strategy against ageism among dental students. Methods: A pre-post prospective study was conducted in three different dental schools located in the State of Sao Paulo, Brazil, that offered geriatric dentistry courses in their curricula. A questionnaire specifically developed for this research and the “Ageism Scale for Dental Students” (ASDS) were applied before and after geriatric dentistry courses in all three dental schools. Results: Among 184 dental students, 51.6% (n = 95) improved their ageism scores. Dental students who improved ASDS scores were more likely to be from a public dental school (56.7% vs. 40.4%; p =.040), in their 8th and 10th semesters (56.7% vs. 40.4%; p =.040), and females (55.6% vs. 36.8%; p =.040). Other factors such as age, ethnicity, history of living with older adults, history of taking care of older adults, and knowledge of ageism were not significantly associated with ageism score improvement. Only institutional affiliation and age remained significant predictors in the final model. Conclusion: In this study, the main variables correlated with reducing ageism among dental students were institutional affiliation and age.